HUBUNGAN PERILAKU CAMAT DENGAN DISIPLIN KERJA SANGAT KUAT DI KANTOR CAMAT SIANTAN KABUPATEN PONTIANAK - Silviana E.42008007, Meita (FISIP Universitas Tanjungpura Pontianak, 2012)
This thesis research aims to test and analyze the relationship between the behavior of the head of district onstrengthening the discipline of the employees in the Head of District’s office of Siantan, Region of Pontianak. Thedata was collected through questionnaires and conducted to 21 employees. The Analysis of the data in this researchusing SPSS 18. The sampling technique using a saturated sampling technique which is the sampling techniqueswhen all members of the population are used as samples and testing techniques of data used in this research is thecontent validity test by testing ‘r count’ > ‘r critical’, with Cronbach Alpha reliability test. To test and prove thehypotheses used product moment correlation coefficient formula.The analysis showed that the behavior of the head of district has a positive relationship with the employeesdiscipline. From the results of hypothesis testing showed that r count equal to 0.842 greater than r table is 0.549 withN amounted to 21 respondents. Based on the results of the r count 0.842 compared to the interpretation of theguidelines table, the strength of the relationship is very strong. From the calculation of the coefficient determinantobtained the contribution of the behavior of the Head of District to the job discipline of the employee in The Head ofDistrict’s office of Siantan,Region of Pontianak, as much as 70.9% and the remaining 29.1% is determined by othervariables outside behavioral variables of the head of district. There is positive relationship in the behavior of thehead of district on strengthening the job discipline of the employee in the head of district’s office of Siantan, Regionof Pontianak.Keywords: the head of district’s behavior, job discipline